Effect of domestic laundering on the fragment protective performance of fabrics used in personal protection. Issue 12 (July 2014) - Helliker, Mark; Carr, Debra; Lankester, Claire; Fenton, Leigh; Girvan, Liz; Horsfall, Ian
UK Armed Forces wear items of clothing that incorporate fragment protective fabrics (Tier 1 Pelvic Protection) and other items of clothing are under development (e.g. Improved Under Body Armor Combat Shirt). The long-term robustness of such garments is of interest. In this paper four candidate fabrics (knitted silk, ultra-high molecular weight polyethylene felt, para-aramid felt and a woven para-aramid) were investigated. The effect of laundering on 0.24 g chisel-nosed fragment simulating projectile ballistic protective performance was measured on packs containing the candidate fabrics that were representative of clothing layers. Changes in the physical properties (mass, thickness, dimensional change) of candidate fabrics were measured. The ballistic protective performance of two candidate fabrics was unaffected by laundering; for the other two fabrics improved performance was measured. The masses of the specimen packs was unaffected by laundering; however, the thickness of all fabrics increased, relative to dimensional change.